Association of rs3135500 and rs3135499 Polymorphisms in the MicroRNA-binding Site of Nucleotide-binding Oligomerization Domain 2 (NOD2) Gene with Susceptibility to Rheumatoid Arthritis - Naeim Ehtesham; Behrang Alani; Deniz Mortazavi; Sara Azhdari; Taiebe Kenarangi; Emran Esmaeilzadeh; Bahram Pakzad (Iranian Journal of Allergy, Asthma and Immunology, 2021)
The nucleotide-binding oligomerization domain 2 (NOD2) is the key regulator of inflammatory responses and has been involved in the pathogenesis of rheumatoid arthritis (RA). Laboratory and in silico evaluations have demonstrated that some polymorphisms in 3ˊUTR of NOD2 gene could influence the secondary structure of this region and similarly thermodynamic features of hybridization site and finally deregulate the expression of NOD2. In the current study, for the first time, we evaluated the possible association between single nucleotide polymorphisms (SNPs) rs3135500 and rs3135499 in the NOD2 gene with RA risk in the Iranian population. One hundred and fifteen patients with RA and 120 healthy subjects were recruited in this case-control study. Genotyping of rs3135500 and rs3135499 polymorphisms were accomplished using the real‑time polymerase chain reaction high resolution melting (HRM) method. We found a substantial association of AA and AG genotypes in rs3135500 with the risk of RA (AA vs GG; OR=5.547; 95%CI [2.564-11.999]; p<0.001 and AG vs GG; OR=2.179; 95%CI [1.145-4.147]; p=0.017). Moreover, in the patient group, there was a significant relationship between the increased concentration of erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) with rs3135500 (A allele) (p<0.05). However, there were no important associations between rs3135499 with the risk of RA (p>0.05). However, we found a noteworthy association of the C allele in rs3135499 with an increased level of CRP in patients (p>0.05). Our findings propose a considerable association between NOD2 polymorphisms with increased risk of RA and disease activity.